Analysis of the steel industry in Russia - D. G. Saginashvili; V. D. Ryabova; M. I. Zakirova (Вестник университета, 2021)
This article presents an analysis of the steel industry in Russia. The external factors of the steel market have been studied. The results of the activities of  steel enterprises for 2019 with the subsequent calculation of the market share of each participant, – have been investigated. The calculation of the main indicators of the market structure in the form of the Herfindahl-Hirschman formulas and the concentration coefficient for the three largest sellers has been carried out. The dynamics of revenue and steel production in Russia by the main producers in the industry market have been estimated, as well as changes in the  level of use of average annual production capacity for a number of products  have been evaluated. The structure of the country’s exports and the influence of the products of the steel industry in it, as well as the factors of its internal and external demand, – have been analysed. Factors and trends of the industry  development have been considered.